2018
DOI: 10.1016/j.jogn.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Experiences Among Chinese American Immigrant Women in the United States

Abstract: Women's health care providers should be aware of and give consideration to cultural differences through the provision of more educational information and comfort to Chinese immigrant women who seek cervical cancer screening. Ultimately, the development of culturally appropriate and affordable cancer prevention programs with effective strategies is important to ease Chinese American women's senses of vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 42 publications
14
18
0
Order By: Relevance
“…Secondly, our results revealed that many women held inaccurate risk perceptions concerning CC. The women in our sample overestimated the role of heredity; similar to ndings in other studies in Iran (27,36) and other countries (53)(54)(55), which is challenging, since the role of genetic causes of CC is still not clear (56), The vast majority of women reported low perceived risk and susceptibility regarding CC, ndings also reported in other studies (33,34,37,53). We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Secondly, our results revealed that many women held inaccurate risk perceptions concerning CC. The women in our sample overestimated the role of heredity; similar to ndings in other studies in Iran (27,36) and other countries (53)(54)(55), which is challenging, since the role of genetic causes of CC is still not clear (56), The vast majority of women reported low perceived risk and susceptibility regarding CC, ndings also reported in other studies (33,34,37,53). We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS.…”
Section: Discussionsupporting
confidence: 92%
“…In concurrence with other studies, our respondents considered CCS as an intervention for STI management (27,(57)(58)(59). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection speci cally) and cervical cancer, and similar ndings have been reported by other studies (33,53). However, the absence of STI symptoms did not make women feel a need to go for screening.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Secondly, our results revealed that many women held inaccurate risk perceptions concerning CC. The women in our sample overestimated the role of heredity; similar to findings in other studies in Iran (27,36) and other countries (52)(53)(54), which is challenging, since the role of genetic causes of CC is still not clear (55), The vast majority of women reported low perceived risk and susceptibility regarding CC, findings also reported in other studies (33,34,37,52). We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also showed that women's knowledge about timing and regulations for CC testing was inaccurate and implicit, and mainly reflected their experiences rather than accurate knowledge. Lack of knowledge and unconfident answers by women regarding timing, frequency and procedures was also reported in other studies (33,52). However, women had detailed, accurate and practical knowledge about terms and conditions for attending CC tests which was not previously explored in other studies.…”
Section: Discussionmentioning
confidence: 70%